THE STRUCTURE AND FUNCTION OF THE CHEEK PADS OF THE BROWN LEMMING, LEMMUS SIBIRICUS (TRIMUCRONATUS) (KERR) - Macpherson, A. H.; Gibson, M. A. (Canadian Journal of Zoology, 1965)
Brown lemmings, Lemmus lemmus and L. sibiricus (trimucronatus), possess thickened pads of skin on the cheeks, and some, at least, also bear a thinner pad on the rump above the tail. The cheek pad is formed chiefly by a remarkable abundance of collagen fibers in the reticular layer of the dermis. The pad appears capable of considerable movement, and is underlain by a well-developed system of dermal muscles. The thickness of the pad appears to be related to age. The apparent function of the pads is to protect the parts of the animal to which bites are directed during intraspecific combat.